Anal anomalies: an uncommon feature of velocardiofacial (Shprintzen) syndrome?. Issue 1 (January 1997) - Worthington, S; Colley, A; Fagan, K; Dai, K; Lipson, A H
Abstract : We report three cases of velocardiofacial syndrome (VCFS) with anal anomalies who have deletions of the 22q11 region and a further case where the proband has VCFS clinically and her father has an anal anomaly. It is important to consider VCFS in the differential diagnosis of children with anal anomalies and to look for other features of the syndrome, such as asymmetrical crying facies, submucous cleft of the palate, developmental delay, cardiac anomalies, and hypoparathyroidism.